Probing Cyber-Bullying Experiences of First Year University Students at a Selected Rural University in South Africa - Tsorai, Precious Pachawo (My University, 2018)
Most people view bullying as a childhood challenge which children outgrow with age. However, bullies grow up and even go to universities where they continue with their bullying tactics; harassing their fellow students. The development of technology has allowed bullying to be taken to adulthood through cyber-bullying. Technology has become a big part of young people’s lives and it plays an increasingly important role in their day-to-day activities. However, it has also become a platform for young people to intimidate and harass each other. Cyber-bullying has become a huge problem for university students, which can cause long term effects to victims. It involves sending hurtful, threatening or embarrassing messages to one another. Cyber-bullying causes problems such as depression, anxiety, suicide, poor school attendance and performance for the victims of such an act. Both males and females take part in cyber-bullying. Avenues for cyber-bullying by students include emails, blogs, text messages, and social network sites such as Facebook, My Space, Whatsapp, Instagram and twitter among others. The main aim of this study was to probe cyber-bullying experiences of both male and female first year students at the University of Venda. Qualitative research approach was used. Snowball sampling, a subtype of non-probability sampling was used to select the respondents for the study. Semi-structured interviews were used as the data collecting tool. The data was analysed using thematic analysis. Confidentiality, anonymity, voluntary participation and informed consent were among the ethical considerations that were followed. The study found that cyber-bullying is prevalent at the University of Venda and it socially, academically, psychologically and physically affects students. More female students were found to be victims of cyber-bullying when compared to male students. In view of the magnitude of cyber-bullying among university students; there is a need for urgent action by the University of Venda management to come up with
MGS
Institute for Gender and Youth Studies
Keywords: Cyber-bullying; UCTD; Cyber-bullies; Cyber-victims; Harass; Probe; Students; Technology; University; 378.19580968257; Aggressiveness -- South Africa -- Limpopo; Bullying -- South Africa -- Limpopo; Education, Higher -- South Africa -- Limpopo; University of Venda -- Students; Computer crimes -- South Africa -- Limpopo